1992
DOI: 10.1099/00221287-138-6-1197
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of an extracellular  -lactamase produced by Acinetobacter calcoaceticus

Abstract: A P-lactamase was purified 430-fold from the culture supernatant of Acinetobacter cafcoaceticus by ion exchange chromatography on CM-Sephadex and affinity chromatography on phenylboronic-acid-agarose. The purified enzyme was homogeneous as judged by SDS-PAGE, and was characterized with respect to molecular mass (38 and 41 kDa by gel filtration on Sephadex G-75 and SDS-PAGE, respectively), pH optimum (pH 7.0), temperature optimum (45 "C) and isoelectric point (9.3). The p-lactamase showed mainly cephalosporinas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
7
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 23 publications
2
7
0
Order By: Relevance
“…Each enzyme was estimated to be pure (Ͼ90%) by SDS-PAGE, and an M r value of 38,000 was calculated (data not shown). Moreover, the pI values calculated in the present study were in all cases Ͼ9.0; these data were in good agreement with those reported by other investigators (2,13,14).…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…Each enzyme was estimated to be pure (Ͼ90%) by SDS-PAGE, and an M r value of 38,000 was calculated (data not shown). Moreover, the pI values calculated in the present study were in all cases Ͼ9.0; these data were in good agreement with those reported by other investigators (2,13,14).…”
Section: Resultssupporting
confidence: 94%
“…The ␤-lactamases produced by Acinetobacter strains can be either plasmidderived enzymes, such as the well-characterized CARB-5 (23) and TEM-1 (15) enzymes, or chromosomally encoded enzymes (20), belonging to group 1 according to the classification of Bush et al (5). The latter enzymes have already been studied in some A. calcoaceticus strains (2,13,20), but comprehensive knowledge of them is still lacking. In particular, production of these ␤-lactamases by other Acinetobacter spp.…”
mentioning
confidence: 99%
“…By examining ␤-lactamases from 30 strains of Acinetobacter, Joly-Guillou et al (17) revealed a cephalosporinase with a pI of Ͼ8.0 in all these strains. Afterwards, Blechschmidt et al (11) reported the purification and biochemical characterization of an extracellular ␤-lactamase with a pI of 9.3 produced by Acinetobacter calcoaceticus. Other attempts have been carried out in order to characterize the A. baumannii cephalosporinase biochemically (25), but nothing has been reported about the gene encoding the enzyme.…”
mentioning
confidence: 99%
“…Several class A, B, and D ␤-lactamases (1,2,3,22,23,27), as well as chromosome-mediated cephalosporinases (pI, Ͼ8) (2, 3) (which confer different resistance phenotypes to A. baumannii) have been described. However, only one ampC gene (AmpC of RYC52763) encoding an AmpC ␤-lactamase (4) and two allelic variants (ABAC-1 and ABAC-2) (17) have been reported so far for A. baumannii strains.…”
mentioning
confidence: 99%